ESTIMATED CONSUMPTIVE USE AND FIELD IRRIGATION REQUIREMENT FOR RICE DURING THE DRY PERIOD: A CASE STUDY IN THE GANGES LOWLAND REGION OF SOUTHWEST BANGLADESH - Muhammad Qumrul Hassan (International Association of Lowland Technology, 2001)
This paper deals with the Consumptive Use (U) and the Field Irrigation Requirement (FIR) for rice crop during the dry period of the Jessore district in the Ganges lowland of southwest Bnagladesh by using the Blaney-Criddle Method. The estimated U ranges from 3.11 mm/d in December to 7.65 mm/d in April. The minimum and maximum estimated FIR for rice crop in the months of December and April is about 3.54 mm/d and 6.61 mm/d, respectively. The total seasonal FIR is about 807 mm for rice crop during the present dry period. The above results may prove useful for the future planning of a rice crop-design calendar of the Jessore district during the dry period